PENGARUH BUDAYA ORGANISASI, EMPLOYEE ENGAGEMENT, DAN QUALITY OF WORK LIFE TERHADAP KINERJA KARYAWAN PT PLN (PERSERO) UNIT INDUK DISTRIBUSI JAWA TIMUR - Wicaksono, Dhanang Yogie Setya; Brahmasari, Ida Aju (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2021)
PT PLN (Persero) East Java Distribution Unit conducts organizational culture transformation programs, employee engagement, and quality of work life for employees with the aim to forming an employee work culture that is in line with core values, fostering strong emotional relationships towards work, and increase employee loyalty to the company, so as to increase employee contribution in order to support continuous improvement of employee performance. This type of research is causal explanatory research. The population in this study were all employees 166 people, the sampling technique used the Slovin method (error 5%) in order to obtain 117 respondents. The data analysis technique used is the validity test, reliability test, and the coefficient of determination. The hypothesis test used is multiple linear regression in the form of the F test and t test. This research was conducted in the city of Surabaya with a research sample of PT PLN (Persero) East Java Distribution Unit. The conclusion proved that organizational culture, employee engagement, and quality of work life partially or simultaneously have a significant effect on employee performance. Suggestions regarding this research are organizational culture, employee engagement, and quality of work life are still the company's main concerns.